ENVIRONMENTALLY SAFE USAGE OF HYDROPOWER POTENTIAL BY HYDROTHERMAL POWER SUPPLY SYSTEMS - Goshovskyi, S.; Zurian, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article contains the results of scientific research and design work related to environmentally safe usage of hydropower potential of the small rivers of the Dnieper basin. The innovative design solutions for extraction of low-grade heat energy of water and systems for its transformation into energy convenient for consumption were offered. It was established that use of renewable low-grade energy of soil is widely used in environmentally safe and economically sound power systems. At the same time hydropower potential is not widely used in hydrothermal heat pump systems. It was proved that existing hydrothermal systems are not always adjusted to actual operating conditions and object location. The evidence was provided that the scientific approach to development of appropriate configuration of hydrothermal collector, to methodology of their optimal mounting and to efficiency determination depending on operating conditions is quite topical issue. The scientific novelty of the new process approach is use of special design of water collector that has modular configuration and consists of several functionally related water sondes. The efficiency of hydrothermal system was scientifically proved. The paper describes the results of experimental research of efficiency of hydrothermal heat pump system where the low-grade heat energy of water is used as a renewable primary heating energy source for functioning of the heat pump. The authors have developed experimental hydrothermal and geothermal heat pump systems to conduct the research. Both collector and ground section of the system have mounted sensors of temperature, pressure and coolant flow velocity. The software for archiving and visualization of obtained data was developed. The research procedure was developed. As part of study, observation data were received and performance efficiency of geothermal and hydrothermal systems was calculated. The comparative analysis of energy systems depending on used renewable energy source was carried out. The conclusion was made that use of hydrothermal heat pump systems is environmentally safe. The data obtained as part of study have great scientific and applied significance for engineering of heat pump energy systems using hydropower potential of the small rivers.